Digital implementation of space vector pulse width modulation technique using 8-bit microcontroller - Faris, Waleed Fekry; Tahir, Ahmad M.; Badran, Marwan A A (International Digital Organization for Scientific Information, 2013)
For several decades, electric drives were used to control the speed of induction motors. The new generations of electric drives are based on high speed power transistors, like IGBT and MOSFET. The main part of electric drive is the inverter which works as DC to AC converter using a power transistor bridge. Since the output of this inverter is a high frequency square wave, a high speed microcontroller is needed to produce the proper switching sequence. Various switching techniques are used to generate PWM signal which is used to determine the amplitude and the frequency of the output voltage. This paper describes the digital implementation of Space Vector Pulse Width Modulation (SVPWM) technique using 8-bit microcontroller for three-phase inverter. The proposed system uses 8-bit PIC16F877A microcontroller to generate SVPWM signal needed to trigger the gates of MOSFET bridge of the inverter. The inverter includes a low-pass LC-filter which is used to give a sine waveform output. The experimental results show the ability of the proposed system to generate a three-phase sine wave signal with desired frequency. © IDOSI Publications, 2013.